2014
DOI: 10.5999/aps.2014.41.6.759
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Treatment of Highly Suspected Nontuberculous Mycobacteria Infections Following Aesthetic Procedures

Abstract: BackgroundInfection caused by nontuberculous mycobacteria (NTM) has been increasing. Awareness of this infection is crucial yet problematic. Delayed management may lead to destructive results. We empirically treated a series of patients with clinical suspicion of NTM infection prior to the identification of the pathogen.MethodsA total of 12 patients who developed surgical site infections between January 2011 and February 2014 were reviewed. Patients with a skin and subcutaneous infection resistant to standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…If there is no clinical improvement of the breast infection despite standard antibiotic therapy, atypical mycobacteria should always be considered as a possible pathogen 4 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…If there is no clinical improvement of the breast infection despite standard antibiotic therapy, atypical mycobacteria should always be considered as a possible pathogen 4 …”
Section: Resultsmentioning
confidence: 99%
“…NTM are a large (more than 170 species classified) and diverse group of ubiquitous, acid‐fast organisms, which are much less virulent than M. tuberculosis. They can produce a wide range of diseases, including infections of the skin and soft tissues 3,4 . Rarely, NTM can cause breast infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). Kim et al [18] also reported a treatment strategy of strongly suspected NTM infections following aesthetic procedures. However, our institution deployed improved strategies of diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics effective against microbial infections-as part of multidrug regimens-should be administered for longer periods. Surgical intervention including debridement, drainage, and massive irrigation can also be effective against such infections [18,19].…”
Section: Discussionmentioning
confidence: 99%